Abdominal surgery as a possible cause of gastric diverticula: Single center one year experience - Abdurrahman Sahin; Mubin Abdullah Ozercan; Ulvi Demirel; Mehmet Yalniz; Ibrahim Halil Bahcecioglu (Medicine Science, 2019)
No Abstract [Med-Science 2019; 8(4.000): 1044-6]